New Insights into Bacillus-Primed Plant Responses to a Necrotrophic Pathogen Derived from the Tomato-Botrytis Pathosystem - Paloma Morales; Máximo González; Ricardo Salvatierra-Martínez; Michael Araya; Enrique Ostria-Gallardo; Alexandra Stoll (Microorganisms, 2022)
Induced systemic resistance (ISR) is one of the most studied mechanisms of plant–microbe interaction and is considered a very promising alternative for integrated pest management programs. In our study, we explored the plant defense response induced by Bacillus velezensis BBC047 in relation to its application before or after Botrytis cinerea infection of tomato plants. The inoculation of BBC047 did not considerably alter the gene expression of the tomato tissues, whereas infection with B. cinerea in BBC047-primed plants induced expression of LRR and NBS-LRR receptors, which are highly related to the ISR response. As expected, B. cinerea infection generated molecular patterns typical of a defense response to pathogen infection as the overexpression of pathogenesis-related proteins (PRs) in leaflets distant to the point of infection. The curative treatment (P + F + B) allowed us to gain insights into plant response to an inverted priming. In this treatment, B. cinerea caused the m tissue damage, extending nearly entirely across the entire infected leaves. Additionally, genes generally associated with early SAR response (<16 h) were overexpressed, and apparently, the beneficial strain was not perceived as such. Therefore, we infer that the plant defense to the curative treatment represents a higher degree of biological stress triggered by the incorporation of strain BBC047 as second arriving microorganism. We highlight the importance the phytosanitary status of plants prior to inoculation of beneficial microorganism for the biocontrol of pathogens.